2020
DOI: 10.1093/cercor/bhaa076
|View full text |Cite|
|
Sign up to set email alerts
|

Localization of Brain Networks Engaged by the Sustained Attention to Response Task Provides Quantitative Markers of Executive Impairment in Amyotrophic Lateral Sclerosis

Abstract: Objective: To identify cortical regions engaged during the sustained attention to response task (SART) and characterize changes in their activity associated with the neurodegenerative condition amyotrophic lateral sclerosis (ALS). Methods: High-density electroencephalography (EEG) was recorded from 33 controls and 23 ALS patients during a SART paradigm. Differences in associated event-related potential peaks were measured for Go and NoGo trials. Sources active during these peaks were localized, and ALS-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…For executive vigilance, ERPs of overall responses were compared as a function of hits or misses in executive vigilance trials and ERPs across time‐on‐task were analyzed as a function of hits in the initial and last period of the task. Epochs were target‐locked (from 200 ms before to 1000 ms after) in executive vigilance trials and ERPs of interest were analyzed by paired t tests in channels based on previous research with signal‐detection tasks (Bonnefond et al, 2010; Groot et al, 2021; Lara et al, 2018; McMackin et al, 2020; Reteig et al, 2019), in particular: P1 (100–200 ms), N1 (140–230 ms), and P3 (350–650 ms) at Pz and SP (500–800 ms) at Cz and adjacent channels. Given that clear peaks were not observed in P1 and N1 in executive vigilance contrasts, ERPs for executive vigilance contrasts were analyzed as a function of adaptive mean amplitude (Martín‐Arévalo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For executive vigilance, ERPs of overall responses were compared as a function of hits or misses in executive vigilance trials and ERPs across time‐on‐task were analyzed as a function of hits in the initial and last period of the task. Epochs were target‐locked (from 200 ms before to 1000 ms after) in executive vigilance trials and ERPs of interest were analyzed by paired t tests in channels based on previous research with signal‐detection tasks (Bonnefond et al, 2010; Groot et al, 2021; Lara et al, 2018; McMackin et al, 2020; Reteig et al, 2019), in particular: P1 (100–200 ms), N1 (140–230 ms), and P3 (350–650 ms) at Pz and SP (500–800 ms) at Cz and adjacent channels. Given that clear peaks were not observed in P1 and N1 in executive vigilance contrasts, ERPs for executive vigilance contrasts were analyzed as a function of adaptive mean amplitude (Martín‐Arévalo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…ERP studies measuring executive vigilance via signal‐detection tasks have found differences in early and late ERPs associated with hits on infrequent signals and correct rejections in the absence of infrequent signals (Karamacoska et al, 2019; McMackin et al, 2020; Reteig et al, 2019). Nonetheless, evidence is both scarce and inconsistent regarding whether the decrease in hits is accompanied by a change in ERPs across time‐on‐task.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated this cortical activation through the combination of quantitative electroencephalography (EEG) and source analysis, which provides excellent temporal resolution with good spatial resolution. We have also demonstrated that disease-related abnormalities in cortical network activation can be interrogated individually using spatially and temporally specific measures to determine the nature of underlying network disruption, even in the absence of impaired task performance [3].…”
Section: Introductionmentioning
confidence: 94%
“… 21 Using this approach with task-based paradigms, we have shown changes implicating dysfunction of the frontoparietal network. 9 , 23 , 24 Furthermore, we have shown that resting-state EEG, which can provide distinct measures that reflect different processes in the brain, 25 can quantitatively capture both motor and cognitive networks affected in ALS. More specifically, using sensor-space analysis, we have found resting-state EEG changes that are correlated with structural changes in MRI 10 and in line with other EEG studies.…”
Section: Introductionmentioning
confidence: 99%